Efektifitas Smartbook Perawatan Paska Seksio bagi Kualitas Pelayanan Keperawatan - Lisa Suarni; Fitarina Fitarina; Sono Sono (Jurnal Kesehatan, 2018)
There are 5 highest causes of maternal mortality which include bleeding, hypertension in pregnancy, infection, prolonged labor, and abortion. One of the prevention and management efforts is to provide immediate and efficient help through hospital services (Ministry of Health, 2014). This research has aims to find the quality of nursing services on patients after cesarean surgery using the SmartBook. Methods: This is Quasi-Experiment that provides treatment with the SmartBook for 4 days in the hospital and assessed nursing services quality. Samples were taken using accidental and random sampling (20 for the intervention group and 21 for the control group). Data was collected using observation sheet and questionnaire, then analyzed with a t-test. Result: There are four variables of nursing service quality (p-value<0.05) indicating significant difference: patient safety, self-care, anxiety, and knowledge of discharge planning, while 2 others (comfort and satisfaction) are not (p-value>0.05). Application of the SmartBook for women following cesarean surgery improves nursing service quality. We suggest further research on nurse and midwife perception about the use of the SmartBook as media of care, both about its use and how far can improve job satisfaction of nurse/midwife.